Pelatihan Smart Research Writing: Transformasi Digital dalam Penulisan Tugas Akhir Mahasiswa STIE Galileo Batam - Hielvita Ludiya; Setyo Widiarto; Priyanto Priyanto; Sulih Wahyudiono (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Scientific writing is a fundamental competency for students, but technical challenges in managing references and formatting manuscripts often hinder the completion of final assignments. This Community Service Activity aims to improve digital literacy and technical skills of STIE Galileo Batam students through "Smart Research Writing" training. The method used is Service Learning (SL), which integrates material presentation with hands-on practice online via the Zoom Meeting platform. The training materials include reference search strategies based on literature linkage mapping using Connected Papers, exploration of scientific sources through publication indexing platforms (Google Scholar, SINTA, and Scopus), automatic reference management using Mendeley, and automation of scientific manuscript preparation using Microsoft Word. The results of the activity showed an increase in participants' abilities in compiling scientific papers more efficiently, accurately, and systematically. However, the team's observations indicated the need to optimize the training duration and adjust the activity schedule to increase participation of students with limited working time. Overall, this training contributed positively to increasing the effectiveness of students' scientific writing processes and supporting ethical and plagiarism-free writing practices.